ВИВЧЕННЯ ПРОБЛЕМИ КВАЛІФІКАЦІЙНОГО РІВНЯ КАДРІВ РСЧА І ВПЛИВУ НА НЬОГО РЕПРЕСІЙ 1937-1938 РР. У МЕЖАХ ПРОМІЖНОЇ ЛІНІЇ ІМПЕРСЬКОГО НАПРЯМУ (Zaporizhzhia Historical Review, 2021)
In the article it is considered history of creation hypotheses of “incompetence” of imperial direction, set and to expose its key positions, set consequences from her.